Economic Growth and Democratic Political System in Developing Countries - Amal, Aloui; Olfa, Saghrouni (Journal of Ecohumanism, 2024)
The relationship between a democratic political system and economic growth has been the focus of debate in recent years. This article is a contribution to the economic analysis of the relationship between democracy and economic growth. Using an econometric illustration of panel data from twenty developing countries, in a period from 2000 to 2021, Fixed-effect, random-effect and GMM model estimates show that a democratic political regime positively affects economic growth in developing countries. This result is explained by the importance of the role of democracy in implementing economic and social reforms, encouraging investment, opening up trade and protecting civil liberties and political powers.